Overconfidence, subjective perception, and pricing behavior - Benigno Pierpaolo; Anastasios G. Karantounias (Federal Reserve Bank of Atlanta, 2017)
We study the implications of overconfidence for price setting in a monopolistic competition setup with incomplete information. Our price-setters overestimate their abilities to infer aggregate shocks from private signals. The fraction of uninformed firms is endogenous; firms can obtain information by paying a fixed cost. We find two results: (1) overconfident firms are less inclined to acquire information, and (2) prices might exhibit excess volatility driven by nonfundamental noise. We explore the empirical predictions of our model for idiosyncratic price volatility.
Keywords: D4; D8; E3; 330; overconfidence; imperfect common knowledge; information acquisition; inflation volatility